Effect of thermal treatment on some properties of lime wood - Olarescu, M. C.; Campean, M.; Ispas, M.; Cosereanu, C. (Springer Science and Business Media LLC, 2014)
Thermal treatment of lime wood was performed in a drying oven at two temperature levels (180 and 200 °C) and for four durations (1, 2, 3 and 4 h). Mass loss, color change, swelling and hygroscopicity were investigated. The dimensional stabilization reached up to 66.4 % and the hygroscopicity reduction up to 33 %, both maximum values being attained at 200 °C/4 h, associated with a mass loss of 9.3 %. The results will be realized in the manufacturing of solid wood panels made of heat-treated lime wood lamellas for outdoor uses.